PREVALENCE AND HISTOPATHOLOGICAL PATTERN OF HELICOBACTER PYLORI IN PATIENTS PRESENTING WITH GASTROINTESTINAL SYMPTOMS: A CLINICAL STUDY.: JPUMHS;2024:14:04,32-40. http://doi.org/10.46536/jpumhs/2024/14.04.558 - Rahid Gul1, Syed Ahmad Shah2, Shaista Alam3, Arbab Muhammad Kashif Khan4, Shafiqullah Khan5, Pordil khan6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Gastritis, peptic ulcers, and the possibility of developing into cancer are among the gastrointestinal conditions that are significantly influenced by Helicobacter pylori H. pylori. This study aimed to evaluate the prevalence of H. pylori and its associated histopathological findings in patients with gastrointestinal symptoms. OBJECTIVE: To assess the prevalence of H. pylori and association with histopathological findings among gastrointestinal symptomatic patients. METHODS: A descriptive cross-sectional study conducted at Khyber Teaching Hospital, Peshawar. About 310 patients were enrolled using non-probability convenient sampling technique. H. pylori stool antigen testing and histological analysis of stomach biopsy samples were examined. Data collected was analyzed by SPSS version 22, with p <0.05 considered significant. RESULTS: In this study, 310 patients were assessed, comprising 171 females 55.2% and 139 males 44.8%. The highest infection rates were observed in the age groups of 31 to 45 18.3% and 19 to 30 15.0%, with an overall positive rate of 16.4%. Histopathological analysis revealed that 134 patients 43.23% had chronic non-specific gastritis, while 140 cases 45.16% presented with Helicobacter pylori-associated pangastritis. There was a significant correlation of H. pylori with histopathological severity was observed p=0.012. However, no significant association of stool antigen test with age p=0.946 and gender p=0.377 was observed. CONCLUSION: Pangastritis and chronic gastritis are the main symptoms of the extremely common Helicobacter pylori infection. Early identification and treatment are essential to prevent complications, even though severe results such as MALT lymphoma are uncommon. Controlling the risks of infection requires routine screening.